HASIL BELAJAR KETERAMPILAN PROSES FISIKA SISWA DENGAN JOYFUL LEARNING DI SMP NEGERI 3 XIII KOTO KAMPAR - Mutiara Rahmadani Putri; Hendar Sudrajad; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study aims to determine learning outcomes and differences in learning outcomes of students' skills of the physical processes in SMP Negeri 3 XIII Koto Kampar using joyful learning. This study is a pre experiment with comparison group design intact. Instruments used in the collection of data is the test result of learning science process skills of physics. Data collection research conducted at the end of the learning process. Physics student learning outcome data were analyzed through descriptive analysis and inferential analysis. Descriptive analysis showed that the increase in learning outcomes of students after learning process skills using joyful learning there was an increase of 9.6 in the low category. Inferential analysis of data obtained from the normal distribution through the calculation using SPSS 21 is obtained t count = 2,526> t table = 2.023 so that there are significant differences in the results of the physics students learn skills through joyful learning.Key Words:learning outcomes, process skills, joyful learning